Machine learning–derived genetic risk scores identify IL21 as a predictor of response to omalizumab and dupilumab in asthma - Akenroye, Ayobami; Zhang, Chengyue; Nopsopon, Tanawin; Kalra, Sean; Weiss, Scott T.; Moll, Matthew R. (Frontiers in Allergy, 2025)
RationaleGenetic risk scores (GRS) of Th1/2/17-related loci may be associated with response to biologics. We leveraged previously published machine learning-derived GRSs associated with plasma proteins from the INTERVAL/UK-Biobank study.MethodsWe assessed 42 Th1/2/17-related GRSs and SNPs for association with response (≥50% reduction in exacerbations) to biologics in 172 White patients with moderate-to-severe asthma in the Mass General Brigham Biobank (MGBB: 92 omalizumab, 38 mepolizumab, 42 dupilumab). Replication was sought in 243 individuals in the All of Us (AoU) cohort (111 omalizumab, 58 mepolizumab, 74 dupilumab). Models adjusted for age, sex, BMI, baseline exacerbations, and principal components 1–10. AUROC was used to evaluate top predictors; type I error was assessed using random GRS sets (target FDR ≤20%).ResultsFemales comprised a large proportion; mean BMI was 28–35 kg/m2. IL21 GRS was associated with omalizumab response in MGBB (OR: 1.7, 95% CI: 1.03–2.87) with similar direction in AoU (1.5, 0.91–2.45). IL21 also predicted dupilumab response in MGBB (2.4, 1.05–5.44) but in the opposite direction in AoU (0.57, 0.31–1.06). IL21 replicated as a predictor of omalizumab [AUROC, 95% CI: MGBB 0.62 (0.50–0.74), AoU: 0.71 (0.61–0.81)] and dupilumab [AUROC, 95% CI, MGBB 0.76 (0.58–0.95), AoU: 0.75 (0.64–0.86)]. Adding IL5RA (omalizumab) or CCL17 (dupilumab) modestly improved AUROC but not significantly. No GRS predicted mepolizumab response.ConclusionsUsing ML-based GRS applied to an independent cohort of asthma patients, we found that IL-21-related GRSs were predictors of response to omalizumab and dupilumab.